Healthcare provider-patient communication: a qualitative study of women's perceptions during childbirth - Precious Madula; Fatch Welcome Kalembo; Hong Yu; Atipatsa Chiwanda Kaminga (BMC, 2018)
Abstract Background There is limited information on the impact of effective healthcare provider-patient communication on facility-based delivery in Malawi. The purpose of this study was to examine the nature of communication in the maternity ward, identify facilitators and barriers to healthcare provider-patient communication, and understand how they affect maternal healthcare. Methods This was a descriptive study that used qualitative data collection and analysis methods. Data were collected through face-to-face in-depth interviews using a semi-structured interview guide to collect information about women's perceptions of their communication with healthcare providers. A total of 30 in-depth interviews were conducted with women admitted for delivery in six health facilities drawn from three administrative regions in Malawi. The information collected focused on the communication that pregnant women had with healthcare providers, their perception of that communication, and the barriers to effective communication. A thematic approach was used for data analysis. Results The main themes that emerged regarding the nature of communication between healthcare providers and patients were: 1) good healthcare provider-patient interaction; 2) verbal abuse and lack of respect; 3) failure by healthcare providers to answer or entertain questions; 4) linguistic barriers to communication and lack of competency in non-verbal communication; and 5) discrimination due to one's status. Conclusion This study has revealed the existence of some communication barriers such as disrespecting and verbally abusing pregnant women, language limitations by some healthcare providers and discrimination due to one's status which are affecting maternal service delivery in some health facilities in Malawi. The study has also shown that pregnant women who are happy with the way healthcare providers communicate with them have the motivation to deliver at a health facility. There is a need, therefore, to develop an intervention that could help healthcare providers to communicate better with their patients.